Electric Field Characteristics of HDPE-NR Biocomposite Under Breakdown Condition - Hishamuddin, Muhammad Amzar Hakim; Mohd Jamail, Nor Akmal; Shee Kandar, Mohd Haris Asyraf; Jerferi, Muhammad Syahmi; Mohd Jamail, Nor Shahida; Kamarudin, Qamarul Ezani (International Journal of Integrated Engineering, 2023)
It is critical to develop new insulating materials that can improve the performance of next generation high voltage cables for creating future electrical networks. The high electric field reduces the resistance of solid insulation and produces partial discharge through imperfections in a dielectric, causing the dielectric to age and eventually fail. Thus, this project seeks to analyse the electric field intensity of High Density Polyethylene (HDPE) in breakdown condition when added with 10g, 20g and 30g of different types of bio-filler such as coconut coir fibre, pineapple leaves fibre, and oil palm empty fruit bunch. This can be achieved by creating a two-dimensional (2D) axisymmetric electrostatic model by using the Finite Element Method Magnetics (FEMM) 4.2 software. The results showed that the unfilled HDPE biocomposites have a higher electric field intensity than 10g, 20g, and 30g biocomposite. This indicates that the maximum electric field intensity changes according to the permittivity and voltage of the bio-filler under breakdown conditions. As a result, the maximum electric field intensity was much lower for HDPE added with a 20g of the pineapple leaves fibre. Hence, pineapple leaves fibre was the best composition as it tends to improve the dielectric properties since it has a lower electric field intensity at the top electrode as compared to other compositions.